Audit Implications of IFRS 17 Implementation on Financial Reporting of Social Health Insurance: Evidence from BPJS of Health - Wondabio, Ludovicus Sensi; Wibisono, Aryo (Institut Bisnis dan Informatika Kesatuan, 2026)
This study examines the implementation of Financial Accounting Standards Statement (PSAK) 117, aligned with IFRS 17, in the Social Security Fund managed by the Social Security Agency on Health, focusing on its implications for financial auditing in social insurance. Departing from prior research on accounting policy alignment, the study analyzes how PSAK 117 affects audit risk, judgment, and complexity due to structural differences between social and commercial insurance. Using a qualitative case study based on regulatory analysis, auditing standards, academic literature, and internal documentation, twelve audit-relevant PSAK 117 issues are evaluated, including contract definition, measurement models, actuarial assumptions, risk adjustment, and the Contractual Service Margin (CSM). Findings indicate that while participant relationships meet contractual criteria, the reliance on actuarial estimates and forward-looking cash flows increases inherent risk. PSAK 117 also elevates audit complexity, requiring greater professional scepticism, substantive procedures, and actuarial expertise under ISA 540 (Revised) and ISA 620. Additionally, the CSM’s conceptual misalignment with the non-profit nature of social insurance introduces further judgment and disclosure challenges. The study concludes that PSAK 117 improves transparency and accountability but necessitates stronger institutional capacity, data governance, and audit guidance, contributing to the limited literature on IFRS 17 auditing in non-commercial contexts.